Morphological and molecular systematics of Shorea section Richetoides (Dipterocarpaceae) in Peninsular Malaysia - Alwan, Ikhlas Hussain (2017)
A phylogenetic study of the Shorea section Richetioides (Meranti Damar Hitam) was conducted by using morphological characters and molecular technique. Shorea is one of the largest genera in the family of Dipterocarpaceae with an estimated 300 species worldwide and there are more than 150 species in Malaysia, of which more than one third is found in Peninsular Malaysia. This genus is distributed from India and Sri Lanka, through western Malaysia, to Philippines and Maluku. The identification of dipterocarps species including Shorea based on morphological characters is not an easy task due to similarities of vegetative characters, and taxonomic classification in deipterocarp have not been supported by their monophyletic origins. Therefore, comprehensive analysis using morphology and molecular studies is required to ascertain their status. Nine fresh samples of Shorea sect. Richetioides were collected from different areas in Peninsular Malaysia and were identified to the species level based on morphological characters. In addition, a new population of Shorea with similar feature of S. kuantanensis that was found in Terengganu, Peninsular Malaysia was included. Shorea kuantanensis, a member of Shorea sect. Richetioides classified as critically endangered species by IUCN Red List and was presumably extinct. This study will clarify the identity and providing a taxonomic evaluation of members in Shorea sect. Richetioides in Peninsular Malaysia because to date, there is no study on the phylogenetic relationship among all Shorea species within Shorea sect. Richetioides. Morphological and molecular analyses were conducted for Shorea sect. Richetioides together with other sections in Shorea. Morphological anaylsis was done using distance method of Neighbor Joining Method (NJ), and molecular analysis was carried out using two phylogenetic analyses methods, NJ and Maximum Parsimony (MP).Two non-coding regions from chloroplast (trnL intron, and trnL-F IGS) were used to construct the phylogenetic trees and rooted with genus Hopea. The morphological analysis confirmed that the newly rediscovered population of Shorea species is S. kuantanensis, and part of monophyletic group of Shorea sect. Richetioides. The monophyly of groups in Shorea is also consistent with the artificial grouping of wood in Shorea i.e., Red Meranti, White Meranti, Balau and Yellow Meranti (Meranti Damar Hitam). Phylogenetic analysis using molecular data also showed similar results on the monophyly of Shorea sect. Richetioides. The use of cpDNA (trnL intron and trnL-F IGS) has provided good resolution in phylogenetic trees and also confirm that the newly found population of Shorea as S. kuantanensis as been found with the morphological analysis.